Rehabilitation of women after mastectomy - proposed procedure - Agnieszka Filarecka; Maciej Biarnacki (Kazimierz Wielki University, 2018)
Breast cancer is a leading cancer among women, high incidence of cancer is not synonymous with high mortality. Women subjected to radical or partial mastectomy after the surgery want to return to full fitness as soon as possible. Movement restrictions associated with surgery do not have a positive effect on the patients' psyche. One of the complications of surgery in the axillary region is damage to the long thoracic nerve. An impairment of the blade mechanics affects the nonergergic movement in the shoulder joint. Using the neurorehabilitation methods, the correct spatula pattern should be reconstructed. Facilitation, or traffic paving, is an effective method used also for peripheral nerve injuries. In each method, the movement is assisted by a therapist who can determine the direction of movement through resistance, or assist it. The study presents examples of activities that can be used in therapy in its various phases. The method of using methods depends on the degree of structural damage and should be modified for the purposes of therapy. A review of available literature and own experience were used for the work.